An Aggressive angiomyxoma in a male patient: A rare case - Damayanti, Nita; Trisnowati, Niken; Kurniawati, Carolina; Suwardjo (Journal of Pakistan Association of Dermatologists, 2022)
Aggressive angiomyxoma (AAM) is a rare mesenchymal tumor commonly affecting perineum of female, but also inflicting analogue area of male in lower incidence. We describe a 22-year-old man with a pedunculated, soft tumor, sized 10x5x7 cm in largest part, on his gluteal sinistra area.Â The tumor was completely excised, and histology examination showed squamous epithelia, spindle- and stellate-shaped cells within myxoid stoma without mitotic figures, fibrosis in some area, and thick-walled blood vessels. No recurrence was observed until 1-year follow-up after surgery.